Advances in Ginseng Tissue Culture Research - Jing, Hongyan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Panax ginseng C.A. Meyer is a traditional and precious Chinese medicinal herb that is widely used in the fields of food, medicine, and cosmetics. This article provides a comprehensive overview of the research progress on Panax ginseng C.A. Meyer tissue culture from four aspects: the current utilization of Panax ginseng C.A. Meyer resources, Panax ginseng C.A. Meyer adventitious root culture, hairy root culture, and elicitor. The aim is to provide a reference for the rapid acquisition of secondary metabolites of Panax ginseng C.A. Meyer and promote the development and sustainable utilization of Panax ginseng C.A. Meyer resources.